KAJIAN PERHITUNGAN DANA PENSIUN MENGGUNAKAN ACCRUED BENEFIT COST - Rezzy Eko Caraka (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2016)
This study aims to (i) Conduct studies and issue civil servant pension fund in Indonesia. (ii) Getting a great value of pension benefits and the present value of pension benefits, (iii) Obtain a plan termination liability and the value of actuarial liabilities. (iv)Obtain normal tuition fees in the defined benefit pension plan and to explain and illustrate the surcharge on funding defined benefit pension plan. Based on this analysis it can be concluded that the calculation of pension funds based on the age of employees is currently appointed as civil servant (y), age of employees (x), limits the retirement age of employees (r), full time of employees (t), the remaining period of the retirement (rx), and a starting salary of employees can be using the concept accured benefit Cost. The government needs to do a review of employee pension payment system should be given attention to the value of the interest rate, large pension benefits, the value of pension benefits, the value of liabilities termination plan and to consider interest rates that do not burden the state budget (APBN).